Extensive left atrial ablation was associated with exacerbation of left atrial stiffness and dyspnea. (29th October 2019) - Moon, Inki; Lee, Seo‐young; Lee, Euijae; Lee, So‐Ryoung; Cha, Myung‐Jin; Choi, Eue‐Keun; Oh, Seil
Abstract: Introduction: The left atrium (LA), including the pulmonary vein antrum, is the main target of catheter ablation for atrial fibrillation (AF). However, there is a lack of data on the effect of extensive LA ablation on LA stiffness. This study sought to investigate the impact of extensive LA ablation on LA stiffness and dyspnea after the restoration of sinus rhythm. Methods: In total, 97 patients with AF (80 patients who only underwent pulmonary vein isolation [PVI] and 17 patients who underwent extensive LA ablation) were investigated. Extensive LA ablation was defined as PVI plus at least two sets of LA linear‐line ablation. LA stiffness was estimated using the ratio of E/e' to global longitudinal LA strain, as measured by echocardiography. The clinical outcomes we evaluated were AF recurrence and composite dyspnea, which we defined as newly prescribed diuretics or hospitalization for heart failure. Results: Patients were 59.3 ± 10.0 years old on average, and 68 (70.1%) were male. There were no significant differences in baseline characteristics or echocardiographic parameters before ablation between the two groups. After ablation, LA stiffness was higher in the extensive ablation group compared with that in the PVI group (0.9 ± 0.6 vs 0.5 ± 0.3, respectively, P = .017). Multivariable linear regression analysis showed that extensive ablation increased LA stiffness ( ß = 0.363, P < .001). AF recurrence was similar in both groups; however, composite dyspnea outcomes were worse in the extensive ablation group ( P = .003). Conclusion: Extensive LA ablation was associated with a worsening of LA stiffness. This might explain dyspnea despite the successful restoration of sinus rhythm.